Responsibilities for DSCC Campaign Lift-off Conference (1968)
The document outlines responsibilities for the DSCC Campaign Lift-Off Conference held in Fresno on January 13–14, 1968. It lists key leadership roles, including Joyce Fadem as Conference Director, Shirley Sklar as Treasurer, and Roy Greenaway as Fresno Arrangements Chairman, along with coordinators for housing, publicity, press, and other logistics. The document also assigns individuals to prepare position papers on major policy areas, organize discussion groups and events such as the legislators' reception and banquet, and manage campaign clinics and materials.